Characterization of nano based drilling fluid for shale swelling inhibition - Abbas, M.A. (Taylor and Francis Ltd., 2022)
Shale swelling is vital causing instability issues with water-based drilling fluids (WBDF). It happens because shale has reactive minerals causing swelling with water. Previously used inhibitors protected clay surface, but nanopores remained open. Physical plugging of nanopores is essential to improve swelling inhibition. Objective of this research is to identify a better shale swelling inhibitor. 0.1â1.1 wt of Multi Walled Carbon Nanotubes (MWCNTs) is used to improve inhibition in bentonite wafers. MWCNTs is characterized by FESEM, TGA, and FTIR. Swelling inhibition, rheological, and filtration properties are determined upto 150 Â°C. MWCNTs based WBDF is also characterized by XRD to study MWCNTs effect on d-spacing. Rheological model study is performed. FESEM determined 94.5 purity, TGA confirmed thermal stability up to 904 Â°C, and FTIR found carbon bonds. MWCNTs has induced 57 swelling inhibition in comparison with base fluid. Rheological and filtration properties are improved potentially, that is, Rheology has improved 57 and filtration 55. Drilling fluid samples are found following shear thinning and Bingham Plastic model with 0.933â0.97 R 2 and lowest RMSE values upto 100 Â°C. In future, MWCNTs can be used with other nanoparticles, polymers, and ionic liquids for swelling inhibition. Â© 2022 Taylor & Francis Group, LLC.